ANALISIS TINGKAT KERUSAKAN DAN VALUASI EKONOMI HUTAN MANGROVE DI PERAIRAN PANTAI DESA NISOMBALIA KECAMATAN MARUSU KABUPATEN MAROS - Haryanto Haryanto; Asbar Asbar; Hamsiah Hamsiah (JURNAL AKUAKULTUR, TEKNOLOGI DAN MANAJEMEN PERIKANAN TANGKAP, ILMU KELAUTAN, 2020)
This study aimed to analyze the potential of mangrove resources in the study area, analyze the damage to mangrove forests in the study area, and formulate management strategies in the research area that repair mangrove damage. The method used in this study is the analysis of the level of damage based on a direct survey of mangrove conditions, interpretation of Landsat 8 imagery for changes in mangrove cover area, interviews and questionnaires for mangrove economic valuations and SWOT analysis for strategic direction directives. results obtained from mangrove conditions for Rhizopora apiculata showed the highest percentage of closure was 57.81%. The results of image interpretation also showed a reduction and additional area from 2015 to 2019 and for the total economic value in the village of Nisombalia at the time of the study amounted to 35,442,557,718 Million Rupiah. There are 2 directions of mangrove ecosystem rehabilitation strategies which are the main priorities in Nisombalia Village, namely: 1) Restoring mangrove functions in accordance with the ecological rehabilitation space pattern, 2) procurement of mangrove cultivation facilities (nurseries and seedlings) which are managed directly by the community.